Stigma in a Collectivistic Culture: Social Network of Female Sex Workers in China - Li, Yuruo; Slopen, Natalie; Sweet, Tracy; Nguyen, Quynh; Beck, Kenneth; Liu, Hongjie (AIDS and behavior, 2022)
In this egocentric network study, we explored Chinese collectivism in relation to social network characteristics and sex work-related stigma among mid-age female sex workers (FSWs). Respondent-driven sampling was used to recruit 1245 mid-age FSWs from three cities in China. We found that a one standard deviation (SD) increase in FSWs’ collectivism was associated with a 0.18 SD decrease in social support (95% CI − 0.32, − 0.04), a 0.20 SD decrease in network effective size (i.e., the diversity of a social network; 95% CI − 0.30, − 0.10), and a 0.21 SD decrease in network betweenness (i.e., the “bridging potential” of egos within their networks; 95% CI − 0.33, − 0.09). Among participants who perceived more sex work stigma, the association between collectivism and FSWs' network betweenness was attenuated. In a collective culture emphasizing group values and honor, belonging to a less interconnected social network may give FSWs a structural advantage to cope with stigma and secure social support.